THE METHOD OF PARAMETERIZATION OF THE PARETO SOLUTIONS IN VECTOR OPTIMIZATION PROBLEMS TO THE SOLUTION OF THE PROBLEM OF DETERMINING THE OPTIMAL COMPOSITION OF A PASSENGER TRAIN - Bosov, A. A.; Kodola, H. M. (Science and Transport Progress, 2007)
The numerical example of the vector-optimization problem decision for a definition rational passenger train composition with the help of a parametrization method Парето of the decision is considered.